2018
DOI: 10.1177/1758835918816287
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cells in hepatocellular carcinoma: an overview and promising therapeutic strategies

Abstract: The poor clinical outcome of hepatocellular carcinoma (HCC) patients is ascribed to the resistance of HCC cells to traditional treatments and tumor recurrence after curative therapies. Cancer stem cells (CSCs) have been identified as a small subset of cancer cells which have high capacity for self-renewal, differentiation and tumorigenesis. Recent advances in the field of liver CSCs (LCSCs) have enabled the identification of CSC surface markers and the isolation of CSC subpopulations from HCC cells. Given thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 213 publications
(274 reference statements)
1
77
0
Order By: Relevance
“…We also showed that PDK1-dependent IR-resistance is associated with the enhanced metastatic and CSCs-like phenotypes of HCC cells (Figure 4 and Supplementary Figure S3). This is consistent with contemporary knowledge that CSCs-like cells exhibit increased resistance to chemo-and radiotherapy compared to their non-CSCs counterparts in same tumor niche [32], even as cells undergoing EMT have been shown to exhibit resistance to genotoxic stress mediated by conventional radio-and chemotherapy [33,34], thus, linking resistance with CSCs-like and EMT-phenotypes. In fact, it was recently suggested that the acquisition of EMT and CSCs phenotypes is linked with the activation of PI3K/AKT/mTOR signaling in IR-resistant prostate cancer cells [11].…”
Section: Discussionsupporting
confidence: 90%
“…We also showed that PDK1-dependent IR-resistance is associated with the enhanced metastatic and CSCs-like phenotypes of HCC cells (Figure 4 and Supplementary Figure S3). This is consistent with contemporary knowledge that CSCs-like cells exhibit increased resistance to chemo-and radiotherapy compared to their non-CSCs counterparts in same tumor niche [32], even as cells undergoing EMT have been shown to exhibit resistance to genotoxic stress mediated by conventional radio-and chemotherapy [33,34], thus, linking resistance with CSCs-like and EMT-phenotypes. In fact, it was recently suggested that the acquisition of EMT and CSCs phenotypes is linked with the activation of PI3K/AKT/mTOR signaling in IR-resistant prostate cancer cells [11].…”
Section: Discussionsupporting
confidence: 90%
“…It is currently believed that the drug resistance pattern of OXA in HCC is mainly related to apoptosis escape, autophagy activation, drug excretion, and enhanced epigenetic transformation to HCC stem cells [25][26][27][28][29]. The EMT process is involved in most models [22,[30][31][32].…”
Section: Rbm8a (Y 14)mentioning
confidence: 99%
“…Cancer stem cells are tumour cells with the ability to self-replicate and differentiate into solid tumours, including HCC 3 , and express known stem cell markers, such as CD133 in glioma, CD44 and CD24 in breast cancer and OV-6 in HCC [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%